2012
DOI: 10.2310/jim.0b013e318235479a
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase Gene Polymorphisms in Neonatal Hyperbilirubinemia

Abstract: Neonates with the GSTM1 null genotype are at high risk to develop pathologic hyperbilirubinemia and may have higher bilirubin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Other studies have also suggested that oxidative stress is the mediator of neurotoxic effect of bilirubin (46). It has been shown that neonate carriers of GSTM1-null genotype are at high risk to develop pathologic hyperbilirubinemia and may have higher bilirubin levels (47). Glutathione S-transferases can act as intracellular binding proteins for nonsubstrate ligands, including bilirubin and bilirubin conjugates, thus decreasing the efflux of bilirubin into plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also suggested that oxidative stress is the mediator of neurotoxic effect of bilirubin (46). It has been shown that neonate carriers of GSTM1-null genotype are at high risk to develop pathologic hyperbilirubinemia and may have higher bilirubin levels (47). Glutathione S-transferases can act as intracellular binding proteins for nonsubstrate ligands, including bilirubin and bilirubin conjugates, thus decreasing the efflux of bilirubin into plasma.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, the authors suggest that the null GSTM1 genotype may affect ligandin functions in hepatocytes, which are important in bilirubin transportation and therefore, patients with the null GSTM1 genotype might have elevated levels of bilirubin [ 53 ]. Abdel Ghany et al also demonstrated that the null GSTM1 variant represents a higher risk of developing hiperbilirubinemia in neonates [ 56 ]. However, in the present study, no statistically significant association was found between null the GSTM1 variant and bilirubin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [24] reported that PBREM and A(TA)7TAA had high linkage disequilibrium among Chinese adults, and functional studies indicated that the combination of PBREM and A(TA)7TAA decreases the expression of UGT1A1 gene. [25] More detailed UGT1A1 genetic sequencing including PBREM and large insertion/deletion, and sequencing for other genes that were reported to cause UCH, such as solute carrier organic anion transporter family member 1B1 (SLCO1B1), [26,27] glucose-6-phosphate dehydrogenase (G6PD), [28] and Glutathione S-transferases (GSTs) [29,30] may shed some light into this phenomenon. Future studies should focus on genetically unexplained UCH cases and find plausible disease causing mechanisms.…”
Section: Discussionmentioning
confidence: 99%